Study Of Different Solar Energy Strategies And Energy Prediction Parameters (International Journal of Food and Nutritional Sciences, 2022)
Solar energy is one of the world's most cost-effective and environmentally friendly alternative energy options. The flow of solar energy is extremely unpredictable due to its dependence on a variety of variables such as weather, seasons, and other environmental/ecological conditions. Estimating solar radiation is an inevitable prerequisite for optimizing solar resources and improving the efficiency of solar systems. The solar industry requires supportive policies to continue its development. Solar power systems and their related technologies have become a common green energy source around the world. Solar energy is not yet widely used in contrast to traditional forms of energy owing to the extremely high cost of building, low conversion rates, and issues with battery capacity. Considering all of this review solar system have a positive outlook future as a solar-powered global powerhouse. This paper studies a comparative analysis between grid extension and the implementation of renewable off-grid hybrid power system. Despite the challenges, numerous advanced materials and approaches to improving the efficiency of solar energy transitions raise the consumer appeal of solar power. In this paper we study the literature from the previous year research paper of promising solar power technologies. This paper also tries to discuss about which type of system used by different authors and also discussed about power generation profile used by different authors.